Development of Tanggomo-Based Teaching Modules to Improve Gorontalo Language Skills in Children in State Kindergartens in Mananggu District - Hiola, Ahmad; Rahman, Misran; Ardini, Pupung Puspa (Universitas Negeri Padang, 2025)
Schools are still lacking and have not even introduced the Gorontalo language to students through school learning. This is because the existing curriculum in schools does not explicitly include Gorontalo language learning materials that are sufficiently in-depth and interesting. One learning innovation in schools to introduce the Gorontalo language is by including Tanggomo oral literature in intracurricular learning in kindergartens. By introducing Tanggomo, teachers have indirectly introduced the Gorontalo language and also introduced the positive attitudes contained in the meaning of Tanggomo poetry. This study aims to create a teaching module containing Tanggomo to improve Gorontalo language skills in children. This research method uses the research and development method. The results of this study indicate that the development of a teaching module containing Tanggomo to improve Gorontalo language skills in children of TK Negeri 02 Tearatai Mananggu has been validated by four experts, namely PAUD experts, design experts, linguists, and Gorontalo language experts and is declared suitable for use with minor revisions.